Multiple regression analysis for the estimation of energy content of municipal solid waste. (8th November 2007) - Agrawal, G.D.; Rathore, A.P.S.; Gupta, A.B.
A regression equation is proposed to predict the Higher Heating Value (HHV) of Municipal Solid Waste (MSW) from the waste data of 86 cities of 35 countries. A mathematical model is developed, by using Statistical Package for Social Sciences (SPSS-10.0), to correlate the energy content of waste with the variables derived from its physical composition. Performance of the proposed multiple regression model is superior to available models. For validation, the proposed model is applied to the waste data of Jaipur City (India), nine cities of EEC countries and also to the MSW of USA. Energy content values obtained by proposed regression model and Modified Dulong's Equation (MDE) are closer to the measured mean energy content values for EEC countries compared to the values obtained by Khan's method. Objective of the paper is to propose a simple model, which can replace the lengthy MDE and which has universal applicability for the predication of HHVs.